DESIGN OF UNMANNED GRENADE TAMER PROTOTYPE WITH WIRELESS CONTROL - Ayip Rivai; Endro Prasetijoadi; Wawan Kusdiana; Mey Edy Prayitno (JOURNAL ASRO, 2020)
Puslatdiksarmil is a military training and basic education center. To support the trainer in securing the grenade during the grenade throwing exercise, the author made "Design of Prototype Unmanned Grenade Tamer with Wireless Control. This tool is used to assist the trainers in the implementation of handling unexploded grenades, by placing a detonator on the grenade then blasting. In the robot control application is very necessary in everyday life and is very helpful in human activities that are dangerous and difficult to do by humans and therefore we need an application that can control the robot remotely. In this Final Project, a robot has been designed that can be controlled remotely by air or wireless media as an application of a grenade tamer robot. Where the design of this robot will use an integrated robot with an actuator to drive the robot, a camera to monitor the location of objects and its surroundings, and a wireless module that has been connected with the 2.4 Ghz Tranciever so the robot can now be monitored remotely to perform operations. Keywords: Unmanned, Wireless, 2.4Ghz Frequency